Measurement and Analysis of Magnetic Properties in IS 2062 Steel and AISI D2 Tool Steel Via Non-destructive Testing - Diwakar V.; Sharma A.; Yusufzai M.Z.K.; Vashista M. (My University, 2025)
Barkhausen noise analysis and hysteresis loop (HL) measurements are effective methods for characterizing ferromagnetic materials. This study employs metrology-enabled non-destructive testing methods to measure and evaluate the magnetic properties of two different types of steel, IS 2062 and AISI D2 Tool Steel, and aims to establish a correlation between their Barkhausen parameters and (HL) characteristics by varying the magnetizing frequency and magnetic field intensity. Additionally, permeability and remanence were analyzed for the low, medium, and high ranges of the magnetizing frequency. The AISI D2 tool steel exhibited a weaker response in terms of peak and root-mean-square values compared to the IS-2062 steel, likely due to its smaller grain size. The average permeability and remanence showed an inverse relationship with respect to the low-frequency range, with the magnitude of average permeability being lower in the AISI D2 tool steel due to its higher hardness level. The study of this research also demonstrated the potential of metrology-enabled non-destructive testing techniques for accurately evaluating magnetic properties in steel, which can be valuable for quality control and process optimization in the steel industry. © 2023, Metrology Society of India.